The Effect of English Choir Activities in English Day Programs on Students’ English Pronunciation and Motivation at SMA Muhammadiyah 4 Bengkulu - Adila; Dian Susyla (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to explore the effect of English choir activities implemented in the English Day program on students’ English pronunciation and learning motivation at SMA Muhammadiyah 4 Bengkulu. This research employed a descriptive qualitative design to describe changes in students’ pronunciation and to examine students’ experiences and perceptions during their participation in English choir activities. The participants consisted of senior high school students who actively joined the English choir as part of the English Day program, with Class X Unggul selected for focused observation. Data were collected through classroom observations and documentation during four English choir training sessions conducted over one month. The findings reveal that English choir activities contributed positively to students’ pronunciation development, particularly in terms of sound clarity, word stress, and intonation. In addition, the activities fostered higher learning motivation, as reflected in students’ increased confidence, active engagement, and willingness to practice English pronunciation during the learning process. The enjoyable and collaborative nature of singing English songs created a supportive learning atmosphere that reduced students’ anxiety and encouraged active participation. These findings suggest that English choir activities can serve as an effective qualitative learning strategy within English Day programs to support students’ English pronunciation development and learning motivation in EFL contexts.